Measurement of Ocular Surface Irritation on a Linear Interval Scale with the Ocular Comfort Index - Johnson, Michael E; Murphy, Paul J (Investigative ophthalmology & visual science, 2007)
To examine the psychometric properties of the Ocular Comfort Index (OCI), a new instrument that measures ocular surface irritation designed with Rasch analysis to produce estimates on a linear interval scale. The OCI was self-completed by 452 subjects. Some of them repeated the questionnaire, to aid in determining its reliability and test-retest repeatability. Ten versions were produced to evaluate question order effects. In addition, three construct hypotheses were tested to verify that the OCI was measuring what was intended, concordance with the Ocular Surface Disease Index (OSDI), the relationship with tear break-up time (TBUT), and the change in TBUT after the use of ocular lubricants in individuals with moderate dry eye. A 12-item OCI was developed with well-functioning items and categories: 95% confidence interval for the intraclass correlation coefficient = 0.81 to 0.91; person separation = 2.66; item separation = 11.12; and 95% repeatability coefficient = 13.1 units (0-100 scale). The ordering of items had no effect on OCI measures (P = 0.41). The OCI measure exhibited a positive correlation with the OSDI score (P < 0.0001) and a negative correlation with TBUT (P < 0.0001) and was able to detect improvement in symptoms of dry eye in individuals before and after treatment (P < 0.0001). The OCI was shown to have favorable psychometric properties that make it suitable for assessing the impact of ocular surface disease on patient well-being and changes in severity brought about by disease progression or therapeutic strategies.